Gestão estratégica do desempenho humano em uma distribuidora de energia elétrica no Brasil: um estudo avaliativo na percepção dos empregados - Lima, Lysia Maria Brito Teles (2012)
In recent years, there has been intense search for organizations by adopting a model of performance management strategy aligned with corporate strategies, so as to simultaneously satisfy all stakeholders. This research aims at investigating the perceptions of employees and managers about the new model of strategic management of human performance adopted by the electricity distributor of Ceará in 2010, called Revenue Management (GR). To this end, consider an evaluation of behavior and achievement of results (goals) aligned with business strategies. Since its inception in 2010, this model was automatically to guide all other shares of the company's personnel management, such as recruitment and selection, training and development, compensation and career. This research is characterized as descriptive in its approach to bringing some quantitative elements. As a method of data collection, we used a sample survey (survey), by means of a questionnaire sent by e-mail. The research was limited to the Companhia Energetica do Ceará (Coelce), its population consisted of employees and managers of the company, totaling 1291 people, and their sample was estimated at 217 participants, corresponding to the number of respondents. Overall, it was concluded that the respondents consider themselves satisfied or very satisfied with the new model of strategic management of human performance by Coelce adopted in 2010. Based on the results of comparison tests, it was observed that the phase of a strategy map was the highest rating, with significantly greater than the average of the remaining phases. Meanwhile, the phases of implementation and overall evaluation of the GR that were reported the lowest average, significantly lower than the other and statistically equal.